An overview of game-based learning in building services engineering education. (3rd March 2016) - Alanne, Kari
Abstract : To ensure proper competence development and short graduation times for engineering students, it is essential that the study motivation is encouraged by new learning methods. In game-based learning, the learner's engagement is increased and learning is made meaningful by applying game-like features such as competition and rewarding through virtual promotions or achievement badges. In this paper, the state of the art of game-based learning in building services engineering education at university level is reviewed and discussed. A systematic literature review indicates that educational games have been reported in the field of related disciplines, such as mechanical and civil engineering. The development of system-level educational games that realistically simulate work life in building services engineering is still in its infancy. Novel rewarding practices and more comprehensive approaches entailing the state-of-the-art information tools such as building information modelling, geographic information systems, building management systems and augmented reality are needed in the future.